here are the problems i need help with. can u tell me the steps to solve these problems?? thank you!(Bow)

first problem: a(x+b)=c

second problem: 9x+2a=-3a+4x

Printable View

- Jul 23rd 2009, 06:25 AMstudent897[SOLVED] solving linear equations in one variable????
here are the problems i need help with. can u tell me the steps to solve these problems?? thank you!(Bow)

first problem: a(x+b)=c

second problem: 9x+2a=-3a+4x - Jul 23rd 2009, 06:38 AMRapha
Hi student897!

What do you mean? Solving for x?

In this case

1) a(x+b) = c

a*x+a*b = c

minus a*b

a*x = c-a*b

divide by a (a is not equal to 0 )

$\displaystyle x = \frac{c-a*b}{a}$

$\displaystyle x = \frac{c}{a}-\frac{a*b}{a}$

$\displaystyle x = \frac{c}{a}-b$

2) 9x+2a=-3a+4x

minus 2a

9x = -3a+4x - 2a

9x = -3a-2a + 4x

9x = -5a + 4x

minus 4x

9x-4x = -5a

5x = -5a

divide by 5

x = -a

Do you understand?

Yours

Rapha - Jul 23rd 2009, 06:49 AMstudent897
i dont like math its always been my worst subjectt! but thnx for the help i sort of get it noww

- Aug 2nd 2009, 09:37 AMstudent897
thnx i understand but i sort of did it in a different way ... the way they taught me in school much less complicated i think.. but thnxxx i understand now

(Headbang) - Aug 5th 2009, 07:10 AMO113
" divide by a (a is not equal to 0 ) "

This is extremely important and a cause for many errors when solving equations.

That being said, the trick is to try to get X alone on one side. Divide, add, remove as much as you have to until it's just X = .....

Might be helpful to repeat some of the basic rules;

$\displaystyle

a(b + c) = a \cdot b + a \cdot c

$

$\displaystyle

d(e - f) = d \cdot e - d \cdot f

$ - Aug 24th 2009, 10:10 PMsyed adnan-ul-haqueNice work
Good........

- Aug 25th 2009, 07:00 AMHallsofIvy
The basic idea is to "undo" whatever has been done to x. In the first problem, I see that two things have been done to x: first b is added to it, then that sum is multiplied by a. We can "undo" that by doing the opposite, in the opposite order: The opposite of "add b" is to subtract b and the opposite of "multiply by a" is to divide by a. And, since I do this in the opposite order, I first divide by a then subtract b. And, of course, whatever I do on one side of the equation, I do on the other to keep them "balanced".

Starting from a(x+ b)= c and dividing both sides by a, a(x+b)/a= c/a or x+ b= c/a since "a/a"= 1. Subtracting b from both sides, x+ b- b= c/a- b or x= c/a- b since b- b= 0.

You may notice that this is not exactly what Rapha did. He chose to "multiply" out a(x+b)= ax+ ab first. But the answer is the same, of course.

The second, 9x+2a=-3a+4x, is slightly more complicated because it has "x" on both sides. We can fix that by getting rid of the "x" on the right- subtract 4x from both sides: 9x+ 2a- 4x= -3a+ 4x- 4x is the same as 5x+ 2a= -3a. Now that has x multiplied by 5 and then 2a added. The opposite of that is "subtract 2a" and then "divide by 5": 5x+ 2a- 2a= -3a- 2a is the same as 5x= -5a. Now divide both sides by 5: 5x/5= -5a/5 is the same as x= -a. - Aug 28th 2009, 05:23 AMstudent897
thnx alot for the help now i think i understand it much better !!!i did it the way u said but at the end i ended up just putting 5x=-5a and then i didnt know what to pput!